The Consideration of Future Consequences: Evidence for Domain Specificity Across Five Life Domains. (May 2020) - Murphy, Lisa; Cadogan, Eimer; Dockray, Samantha
The consideration of future consequences (CFC) is a cognitive-motivational construct describing the extent to which individuals consider the future outcomes of behavior during decision-making. The current research examined the extent to which CFC may be a domain-specific, as opposed to global, temporal construct. Across three surveys, adults ( n = 498; 66.9% female; 41.2% students) completed the 14-item general CFC scale, five newly adapted domain-specific CFC scales, and self-report measures of behavior in five substantive domains (work, health, the environment, money, and college). Confirmatory factor analyses replicated the two-factor model in the CFC-14, supporting the distinction between CFC-Future and CFC-Immediate in domain-specific CFC-14 scales. Hierarchical regression analyses indicated that domain-specific, and not the general, CFC subscales were most strongly associated with the relevant domain-specific behavior and revealed differential patterns of association between domain-specific CFC subscales and behaviors in particular domains. The applied implications for behavioral interventions are discussed.